PENGEMBANGAN SABUN LERAK CAIR RAMAH LINGKUNGAN UNTUK PERAWATAN BATIK ECO-PRINT DI SLB PELITA BUNGA - Maulana, Frendi; Mutmainah, Siti; Maulita Purnama Sari, Eny; Aini, Nurul; Mariana, Erni (Jurnal Abdi Insani, 2025)
Synthetic detergents pose significant health and environmental challenges. While Sapindus rarak DC offers a safe, abundant natural soap alternative, its utilization remains limited due to insufficient public knowledge and processing skills. This community engagement activity aimed to enhance the understanding and practical skills of teachers at SLB Pelita Bunga in processing lerak into eco-friendly liquid soap, developing a production site plan, and supporting the school's entrepreneurship, particularly for eco-print batik care. Utilizing a participatory action learning approach, the method involved five main stages: preparation, literacy education, hands-on liquid lerak soap production training (including direct application for washing eco-print batik), business site-plan assistance, and packaging and marketing strategies. Evaluation results demonstrated a 100% participants' understanding and their successful independent production of liquid lerak soap. The program's strength lies in its applicable training method and direct integration with the school's existing eco-print batik entrepreneurship. However, challenges included manual saponin extraction and a short product shelf-life (2-3 weeks). In conclusion, this training successfully enhanced the capacity of SLB teachers in liquid lerak soap production, significantly supporting the school's independence and diversification of eco-friendly entrepreneurial products.